2002
DOI: 10.1053/joca.2002.0814
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structural organization of normal adult human articular cartilage

Abstract: A comparison of these normal human quantitative data with those published for experimental animals commonly used in orthopaedic research reveals substantial differences, consideration of which in tissue engineering strategies destined for human application are of paramount importance for successful repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
381
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 435 publications
(423 citation statements)
references
References 33 publications
26
381
1
7
Order By: Relevance
“…Due to methodological differences, direct comparisons with other studies are difficult. However, to compare our results to previous studies, we calculated the ratio between the densities of the superficial zone and the deeper zones and found that it was comparable to those of other studies (Hunziker et al, 2002;Quinn et al, 2005;Temple et al, 2007).…”
Section: Cell Density and Split Linessupporting
confidence: 88%
See 3 more Smart Citations
“…Due to methodological differences, direct comparisons with other studies are difficult. However, to compare our results to previous studies, we calculated the ratio between the densities of the superficial zone and the deeper zones and found that it was comparable to those of other studies (Hunziker et al, 2002;Quinn et al, 2005;Temple et al, 2007).…”
Section: Cell Density and Split Linessupporting
confidence: 88%
“…Interestingly, our results showed no differences between the superficial densities of the different articular surfaces that were analyzed (Figure 5), suggesting that the observed spatial, numerical and proximity based differences were local occurrences whose presence did not affect the bulk cell density. As shown previously for articular cartilage (Hunziker et al, 2002;Quinn et al, 2005;Stockwell, 1971), all cartilages of the knee and ankle joints showed significantly higher cell densities in their superficial zones than in their corresponding deeper zones (p < 0.05). In the shoulder and elbow joints, a trend to higher superficial than deeper zones cell densities was observed.…”
Section: Cell Density and Split Linessupporting
confidence: 81%
See 2 more Smart Citations
“…[3][4][5] The composition of articular cartilage varies with the zones, with the superficial zone showing the highest collagen content and cellularity and the lowest proteoglycan content. [6][7][8] Proteoglycan content has generally been shown to be highest in the middle zone. 8 In osteoarthritis, degenerative changes in the articular cartilage and other joint tissues result in pain, swelling, and decreased range of motion of the joint.…”
Section: Introductionmentioning
confidence: 99%